PHARMACOECONOMICAL EVALUATION OF INVASIVE CANDIDOSIS PREVENTION IN THE NEONATES WITH VERY LOW BODY MASS - A.S. Kolbin (Педиатрическая фармакология)
Invasive candidiasis in premature neonates is characterized by frequent and attributive mortality. The authors carried out clinical and economic analysis of invasive candidiasis prevention in neonates with very low body mass at the delivery by means of flukonazol in the doses of 3 and 6 mg/kg. 104 neonates receiving prophylactic treatment with flukonazol comprised the main group, 249 prophylaxis free neonates comprised the control group. The study was prospective, analytical, randomized, cotrolled and clinical. such pharmacoeconomical analyses as disease cost, minimization and effectiveness of expenses were used. the study demonstrated that the greatest direct expenses in the process of candidiasis treatment were for hospital stay (81%) and the least ones for flukonazol (4%). pharmacoeconomical analysis of the obtained data showed that prophylactic dose of 3 mg/kg of flukonazol is more effective than that of 6 mg/kg or keeping premature prophylaxis free neonates in the ICU.Key words: invasive candidiasis, very low body mass at the delivery, pharmacoeconomical analysis, premature neonates.